PENGARUH ATRIBUT PRODUK DAN BAURAN PROMOSI TERHADAP ETIKA JANJI DALAM KONTEKS SERVICE MARKETING TRIANGLE DAN IMPLIKASINYA PADA KEUNGGULAN BERSAING PERGURUAN TINGGI - K. Prihartono A.H. (Indonesian Journal of Economics and Business, 2012)
Promises ethics in service marketing triangle context at the Polytechnic in Kopertis IV Region of West Java and Banten can be met if performance improved product attributes and implementing promotion mix as well, so that promises ethics of Polytechnic can be achieved optimally and given the implications for competitive advantage of Polytechnic. The purpose of this study was to analyze and determine the effect of product attributes and promotion mix to promises ethics in service marketing triangle and its implications on competitive advantage of polytechnics in Kopertis IV Region of West Java and Banten. The research method used is survey method, namely descriptive and explanatory. Number of respondents in the study 330 students of polytechnics in Kopertis IV Region of West Java and Banten, which is determined by sampling technique, which is cluster proportional random sampling. Hypothesis testing is done using a multivariate statistical test of the Partial Least Square (PLS). Data processing is done by smartPLS 2.0 programs and Statistical Programs of Social Science (SPSS) for Windows. The results showed: (1) The product attribute, promotions mix, The promises ethics in service marketing triangle context and the competitive advantage of Polytechnic in Kopertis IV Region of West Java and Banten indicates good condition; (2) The product attribute and promotions mix affect the promises ethics in service marketing triangle context of Polytechnics in Kopertis IV Region of West Java and Banten; (3) The product attribute and promotion mix effect the competitive advantage of Polytechnics in Kopertis IV Region of West Java and Banten ; (4) The promises ethics in service marketing triangle context effect on the competitive advantage of Polytechnic in Kopertis IV Region of West Java and Banten; (5) The product attribute and promotion mix effect through the promises ethics in service marketing triangle context against for competitive advantage of Polytechnic in Kopertis IV Region of West Java and Banten.